Expected Versus Real Effects and Challenges of Urbanization in Albania During the Transition: A Focus Group-Based Assessment - Osmani, Myslym; Ergen, Mustafa (European Scientific Journal, ESJ, 2019)
This paper focuses on learning about the characteristics, effects, and challenges of the urbanization in Albania during transition. Key research point involves assessing how much effective urbanization was. Focus group discussion was the research method used. Major findings about the urbanization in Albania are: an unplanned process, weak and incomplete legislation, weak public management capacities, conflict, and widespread informality. Reduction of poverty and unemployment are positive effects, but a significant gap exists between expected and real effects (-4 and -3.9, for employment and poverty). Disappointing is an effect on education quality and climate for private business activities. In general, negative effects out-passed significantly the expected ones by 2.6 points. Major negative effects are increased crime, congestion and pollution, reduced green area, loss of family bonds, and some loss of traditions and rural values. Major challenges in the future include efficient management of land, improving quality of education, reduction of informality and illegal economic activity, and guaranteeing land property rights. In conclusion, urbanization in Albania was a deficient process. This is with positive effects and also with harsh negative consequences and tough challenges ahead. Managerial and policy recommendations, and propositions for further research, are provided at the end of the study.